Analysis of the Implementation of Total Quality Management in Improving the Quality of Hemodialysis Services at Bangkinang Regional Hospital in 2023 - Meri Sartika Raharta*; Budi Hartono (Riwayat: Educational Journal of History and Humanities, 2023)
Total Quality Management (TQM) provides a form of quality control for the Total Quality Management (TQM) provides a form of quality control for the services provided, including hemodialysis services, which are superior services at Bangkinang General Hospital. The problem is that there are indicators for the quality of hemodialysis services that do not reach a minimum service standard of 100% and the level of patient satisfaction is still low, namely 73.2%. The aim of the study was to analyze the implementation of Total Quality Management in improving the quality of hemodialysis services at Bangkinang General Hospital in 2023. This type of qualitative research uses a phenomenological approach. There were 11 informants, namely the director, chair of quality improvement and patient safety, chair of the nursing committee, head of the room, doctor in charge, executor, nurse, administration and patient. The triangulation used is source, method and data triangulation. The results showed that the inputs (human resources, financing, facilities and infrastructure, machines and SOPs) had not yet reached the minimum hospital service standards. The HD service process is based on 10 long-term TQM elements, teamwork, continuous system improvement, education or training, controlled freedom, unity of purpose, employee involvement and empowerment) and the output does not yet meet service quality patient safety, efficient, effectiveness, timelines, patient centered and equity. The main obstacles to improving the quality of HD services are budget constraints for procuring training, facilities and infrastructure and the low compliance of staff in implementing a culture of quality and patient safety. Bangkinang Hospital can use the Value Stream Mapping method for budget control, Failure Mode Effect Analysis to analyze problems in HD services, conduct Public Private Partnerships through operational cooperation to add HD machines, Contracting-out with training institutions and private companies in procuring and funding HD training and others. Re-socialization of universal precautions and patient safety to officers in the hemodialysis room